PENGARUH PERANAN WALI KELAS TERHADAP DISIPLIN SISWA DI SMK NEGERI 2 PEKANBARU - Yuli Ristiani Dewi; Gimin Gimin; Jumili Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the problems that arise from the observations made by researchers ie students in SMK Negeri 2 Pekanbaru on the role of homeroom who has not implemented its role maximally to the discipline of his students. Many found guardians who seem indifferent with the students because the homeroom considered their duty just teach it but also as a mentor. This study aims to describe the influence of the role of guardian against the discipline of students in SMK Negeri 2 Pekanbaru by looking at the answers of students to the questionnaire given to 60 students. The method used in this research is descriptive quantitative, the data in the analysis by using simple linear regression. Based on the research results can be concluded that there is a significant influence between the role of guardian against the discipline of students SMK Negeri 2 Pekanbaru because it turns Fhitung ≥ Ftabel or 83.850 ≥ 4.01. Based on calculation result known R square value equal to 0,591 or 59,1% mean, that contribution of class guardian role in to student discipline in SMKN 2 Pekanbaru 59,1%, while 41,9% (100-94%) influenced by variable not included in this study. Based on data analysis the role of guardian classified as very high that is equal to 76.30%, while the discipline students in SMK Negeri 2 Pekanbaru classified good category that is equal to 69.89%.Keywords: Homeroom Teacher, Discipline Students